Structural analysis of organic compounds by combined application of spectroscopic methods - Clerc, Thomas; Pretsch, Erno, 1942-; Seibl, Josef, 1924- (Studies in analytical chemistry ;, 1981)
Structural Analysis of Organic Compounds by Combined Application of Spectroscopic Methods.